‘Used and Amused’: On Having Been a Real-Life Model, Muse, Performer, Poseur, and Sitter - Spaid, Sue (Aesthetic Investigations, 2023)
On the occasion of this special issue focused on Models and Sitters, I am presenting what Dawn Kanter (in this issue) terms a ’textual account of the sitter’. With this in mind, I revisit a particular era in my life (primarily 1993-1999) when I regularly served as a model, muse, performer, poseur, and sitter. In fact, there was sufficient material to organise ’Used and Amused’ (2000), an exhibition focused on ten collaborations, for which I typically self-improvised. Rather than simply detail these events, I’ve woven various ideas developed by each of this special issue’s contributors into this article, so that my narrative here augments their papers.